Investigating the Interconnection Between Learning Styles, Language Learning Strategies, and Gender Among English Foreign Language (EFL) Learners - nesi ramadhani; Absharini Kardena (BiCED Proceeding, 2024)
English language learning strategies and learning style for english foreign language ( EFL) is such a challenging aspect for the teacher in teaching english. The more teacher can provide those things the more effective learning in the classroom. In another side, gender is one of the factor that influence english language strategies and students learning style . whether it is male or female can make the diferenciation on students own learning style.therefore, By conducting descriptive and corelative method this study aimed to identify the major, minor, and negligible perceptual learning styles of the students. Additionally, the language learning strategies employed by the students will be examined. the data were collected through two kind of questionares which are PLSQ and SILL where the participants are 24 students at junior high school at MTI Paninggahan At seventh grade. The findings of the research showed that gender differences only works in compensatory strategy especially for female students then correlation study identify that there was a significant relationships between visual styles, cognitive and metacognitive strategies between auditory style and cognitive and compensatory strategies. Hence, social strategies is corelated with tactile, group and individual style. However there are many study related to this study but there is no study that focused on the students at first grade of junior high school especially for those students who doesn’t learn English as foreign language at their elementary school. In fact, The result of this research is beneficial for teacher in teaching and employing the suitables strategies with the students learning style